The induction of anomalous experiences in a mirror-gazing facility: suggestion, cognitive perceptual personality traits and phenomenological state effects. - Terhune, D; Smith, MD (2006)
Previous research suggests that mirror-gazing is efficacious for the facilitation of anomalous experiences. The present experiment tested the hypothesis that the incidence of such experiences is a function of the demand characteristics of the procedure. Participants were randomly allocated to one of two conditions and completed a battery of trait and state measures. Individuals who were given suggestions for anomalous experiences, relative to those who were not, reported a greater number of visual, and a suggestively greater number of vocal, hallucinations. The experience of a descriptively dissociative phenomenological state was the strongest predictor of the reporting of anomalous experiences, but only correlated with the experience of anomalous perceptions in the suggestion condition. Experients of visual apparitions were found to significantly differ from nonexperients in their preference for a visual cognitive style independently of condition.